2017
DOI: 10.1002/14651858.cd003289.pub6
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco cessation interventions for young people

Abstract: Analysis 2.4. Comparison 2 Comparison of theoretical basis of behavioural interventions, Outcome 4 Complex theoretical model with stage of change, motivational interviewing, cognitive behavioural therapy and/or social cognitive theory vs control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
130
3
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 268 publications
3
130
3
10
Order By: Relevance
“…Furthermore, comprehensive interventions are considered necessary for effectiveness. Previous research has shown that the complex interventions, including multiple mechanisms of change, are most effective (Fanshawe et al, 2017). A possible add-on to GNG trainings is attentional bias modification (ABM), in which the attention of participants is trained away from the targeted stimuli (i.e., smoking pictures) and towards neutral or control stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, comprehensive interventions are considered necessary for effectiveness. Previous research has shown that the complex interventions, including multiple mechanisms of change, are most effective (Fanshawe et al, 2017). A possible add-on to GNG trainings is attentional bias modification (ABM), in which the attention of participants is trained away from the targeted stimuli (i.e., smoking pictures) and towards neutral or control stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Future research will have to examine these processes, and identify and measure key behavioral variables involved in the process of change. Tobacco use among teenagers remains a problem, however, most tobacco control programs for adolescents are based around the prevention of initiation of smoking or tobacco use 27 . In the Indian context, tobacco prevention and life-skills programs have been implemented for adolescent cohorts, and some have even demonstrated effectiveness in trials 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Various tobacco cessation interventions for adolescents have been tested globally, including psychosocial and behavioral approaches (such as school and community-based programs, pharmacotherapy, and tobacco control policies), but these interventions had mixed results 30 . It appears that the most significant therapeutic effect in teenagers was observed for self-monitoring and coping skills, motivational strategies (reducing ambivalence to change), group counselling, and addressing social influences that affect smoking behavior 27,[30][31][32][33] . The National Tobacco Control Program in India has made provisions for cessation services, a national quitline, and mobile-phonebased cessation support program 24 , yet, tobacco cessation interventions designed specifically for adolescents are few in the country.…”
Section: Discussionmentioning
confidence: 99%
“…The transtheoretical model (TTM) is an empirically validated model of individual behavioural change, which involves progress through a series of stages to make a particular behavioural change (Leer, Hapner, & Connor, 2008). TTM-based interventions have been applied to facilitate health behavioural changes, such as physical exercise (Pinto, Dunsiger, Farrell, Marcus, & Todaro, 2013), smoking cessation (Fanshawe et al, 2017;Spencer, Adams, Malone, Roy, & Yost, 2006) and weight management (Lee, Park, & Min, 2015), studies of which continue to demonstrate positive effects. As far as we know, there have been few studies of patients with an ostomy using TTM as an interventional tool to provide continuous and dynamic education.…”
Section: Introductionmentioning
confidence: 99%